Driving License Management Services In Preventing Traffic Accidents - Puguh Agung Dwi Pambuditomo; Widayati Widayati (Universitas Islam Sultan Agung, 2020)
In the Blora Police jurisdiction, the number of traffic accidents from year to year has increased. One of the efforts to reduce the rate of traffic accidents is by making SIM services according to the correct procedure. The purpose of this study was to determine and analyze the service for making a driving license (SIM) at the Blora Police in order to prevent traffic accidents and to find out and analyze the obstacles faced by the Blora Resort Police in making a driving license and their solutions. The approach method used is sociological juridical, descriptive analytical research specifications. Types and sources of data are primary data and secondary data. The data collection methods are field studies and literature studies. The data analysis method uses qualitative analysis. The theory of public service, law effectiveness and benefit theory is used as an analysis knife. The results showed that the service for making a driving license (SIM) at the Blora Police in order to prevent traffic accidents has been implemented in accordance with applicable statutory procedures and can be said to be effective in reducing accident rates. The problem faced by the Blora Resort Police in making a driving license is the lack of number of personnel. The solution is to divide the service into two groups, namely applicants for new SIM and applicants for SIM extensions; the timeliness of service is not in accordance with the SOP, the solution is to immediately take a theoretical test every time a participant has a If there is equipment damage in the SIM service, the solution is to wait for the technician to arrive while still performing services using the available equipment; and lack of public awareness and understanding, the solution is by socializing the community.